PENTINGNYA PELAYANAN KESEHATAN KEPADA NARAPIDANA MUDA DI LEMBAGA PEMASYARAKATAN: THE IMPORTANCE OF HEALTH SERVICES TO YOUTH IN CORRECTIONAL INSTITUTIONS - Damanik, Benny Syahputra; A.K.S., Ali Muhammad (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
Young prisoners’ health needs represent a matter of constant importance for any prison administration. These are addressed through direct medical services, as well as through other activities of health promotion. If the medical services are provided by trained medical staff, health promotion is usually provided by non-medical staff, such as social workers, psychologists, educators etc. Also, because healthy behaviors are best promoted through social modeling, such activities require the involvement of all prison staff, including non-specialists such as guardians. Thus, for health promotion to be effective it needs to be approached by the whole prison staff, meaning that the medical and non-medical specialists, as well as other prison staff need to have a common understanding of young prisoners health needs and to work as a team. This can be done through prison staff training. The article addresses these issues by summarizing the Indonesia country reports of the project “Health Promotion for Young Prisoners” funded in the framework of the Public Health Program.